Implementing a Simplified Risk Management Approach in Agile Software Development: An Experience Report - Santos, Julio Cesar dos; Coelho, Vicente Pinto Alves; Fonseca, Felipe Mello; Mendonça, Diogo Silveira (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
Agile software development projects often overlook risk management. Besides that, the lack of risk management could lead to problems such as delays, budget overruns, and even project termination, especially in distributed software development. In this paper, we address this topic in an industrial context. We implemented a simplified method to manage risks in distributed agile software development projects at Betabit company. The risk management approach proposed includes identifying, recording, and monitoring the risks faced by the company during its projects, enabling the creation of action plans to handle the risks. We assessed the acceptance of the method by applying the Technology Acceptance Model (TAM) questionnaire and open questions among the professionals who used it. The research results showed that the model was well accepted, with 90.1% of participants agreeing that it was useful in risk prevention and management. The benefits found were a broader view of projects, effective communication among teams, knowledge sharing, task clarification, and a structured approach to risk management. The challenging part is to learn how to use the method. Besides that, all respondents would recommend the proposed method to other companies, showing the potential of the method to manage risks in agile software projects.